Pelatihan dan Pendampingan Melalui Digital Marketing, Legalitas dan Manajemen Keuangan dalam Pengembangan UMKM di Kelurahan Plosokerep Kota Blitar - Diah Rahmadani; Chrystia Aji Putra; Aldien Ramadhan; Alifia Oktaviani Sastra; Yumna Putri Salsabil; Bagus Wahyu Tri Pambudi; Arifiana Nur Hanifah; Indah Nur Hamidah; Reyhan Abiyyu Hartono; Abrar Athaya Yuris Erbinavydho (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the sectors that are well-known for the impact of the Covid-19 pandemic. This impact makes people's purchasing power decrease, and many consumers switch to making online purchases. So it is necessary to provide assistance to MSMEs regarding digital marketing through market places and marketing content, the importance of legality in easy business development, as well as skills for MSME businessmen to manage finances. The target of this community service activity is the owner of MSMEs in Plosokerep Village, Sananwetan District, Blitar City. The implementation method used in this community service is the training method and door to door assistance for each MSME actor. Evaluation of the activities used in this community service is an element of skills and knowledge. The training provided by the 141 Thematic KKN MBKM UPN “Veteran” East Java group regarding the digitization of MSMEs succeeded in changing MSMEs in Plosokerep which were initially still conventional to digital. The purpose of this activity is that business actors can use the internet and technology to support product marketing and expand the reach of the target market through digital marketing.